Zone based Multi-Agent with Multi-hopRouting in MANET - Sultanuddin S.J, Mohammed Ali Hussain (Journal of Information & Systems Management, 2018)
Mobile Ad hoc Network (MANET) comprises of thousands of mobile nodes spread across the network. These nodes are highly mobile which possess some inherent characteristics like node reliability, resource heterogeneity, etc. In this paper, we proposed a Multi-Agent Based Multi-hop Routing (MAMR) protocol for MANETs. Our proposed MAMR protocol comprises of multiple agents including static and dynamic mobile agents. The operation of our proposed scheme is as follows: (i) At first, the zone leaders are discovered; (ii) These zone leaders are connected with communication nodes, (iii) Back bones are built by employing communication and zone leaders to achieve multicast routing, (iv) Zone members of multicast are connected to the backbones, (v) In case if the nodes are highly mobile, backbone and zone managements are initiated. In MAMR protocol there are five kinds of agent nodes are used in which Path agent, Network control agent and Multicast control agent are static; Network launch agent and Multicast control agents are mobile. The performance of the proposed system is evaluated under several network conditions in which packet delivery ratio, delay and throughput are measured. The proposed protocol is compared with Multicast Routing Protocol Based on Zone Routing (MZRP), On-Demand Multicast Routing Protocol (ODMRP). Through the obtained simulation results it is clearly shows that MAMR protocol performs better than MZRP and ODMRP. This also offers better flexibility and versatile multicast services.